Fortaleciendo escenarios educativos de paz desde el análisis de la normalización y la detección oportuna del acoso escolar en las prácticas pedagógicas docentes (2023)
Bullying is a form of violence that occurs in schools and can have serious consequences for the victims. It is characterized by physical, verbal or emotional violence that is repeated over time and occurs between students in the same school. The normalization of bullying by teachers is a factor that hinders the detection and treatment of cases. Teachers who normalize bullying tend to tolerate or ignore these behaviors, which makes victims feel alone and unsupported. This phenomenon has a negative impact on the school climate and on the development of students, as victims of bullying may suffer physical, psychological and emotional damage, and have difficulties in learning and in relating to others. This work is the result of a research project that aims to analyze how the normalization of bullying by teachers affects the detection and care of cases. It is expected that the results of the research will help to socialize the characteristics of bullying, so that appropriate pedagogical tools and strategies for its detection and prevention can be designed and implemented.